17: Examining the Utility of Hormone Levels in Predicting Healthy Body Weight in Youth with Restrictive Eating Disorders. Issue 6 (1st June 2014) - Maszczakiewicz, E; Obeid, N; Norris, ML; Harrison, M
Abstract: BACKGROUND: Return of menses (ROM) is a well known objective determinant of health in adolescents with eating disorders (EDs), and is helpful in predicting a target weight treatment goal to which the patient should be working towards. Although weight gain is a well known prerequisite for re-establishing a normal menstrual cycle, the degree of weight gain required, the predictors and the temporal association between weight and menstrual resumption have not been well established. OBJECTIVES: The primary aim of this study was to examine the relationships between hormone levels (estradiol, LH, FSH), body mass index (BMI), percent body fat and menstrual status in patients with a restrictive ED to ascertain whether these indicators were helpful predictors of ROM. The secondary goal was to compare hormone levels in patients who achieved ROM with those who remained amenorrheic with the aim of better understanding the role of hormones in ROM. DESIGN/METHODS: A retrospective chart review was completed on a random sample of 100 patients diagnosed with a restrictive ED (anorexia nervosa, eating disorder not otherwise specified) between November 2001 and December 2011. Demographic information, BMI, hormone levels, bone density scores, percent body fat and menstrual history were examined. RESULTS: Patients with restrictive EDs who have menses at assessment differed from those with secondary amenorrhea in that they had higher BMI (19 kg/m 2 vs 16.4 kg/m 2 ); higher percentage of their healthy body weight goal (89% vs 79%); longer chronicity of symptoms (20.3 vs 16.4 months); higher estradiol levels (196 vs 86) and higher body fat percentage (25% vs 14%). Preliminary analyses reveal largely variant hormone levels existed across the groups, although themselves were not found to be predictive of ROM. CONCLUSIONS: Patients with restrictive EDs with and without menses differed at assessment with regard to their hormone and weight profiles, although these indicators were not found to be predictors of ROM. These findings agree with current literature that serum sex hormones are not sufficiently precise for prediction of ROM at an individual level. More research is required to delineate predictors of ROM in amenorrheic adolescents with EDs in order to help inform accurate healthy body weight predictions.